2005
DOI: 10.1152/ajpgi.00223.2004
|View full text |Cite
|
Sign up to set email alerts
|

Natural resistance to liver cold ischemia-reperfusion injury associated with the hibernation phenotype

Abstract: . Natural resistance to liver cold ischemia-reperfusion injury associated with the hibernation phenotype. Am J Physiol Gastrointest Liver Physiol 288: G473-G480, 2005; doi:10.1152/ajpgi.00223.2004.-The success of liver grafts is currently limited by the length of time organs are cold preserved before transplant. Novel insights to improve viability of cold-stored organs may emerge from studies with animals that naturally experience low body temperatures (T b) for extended periods. In this study, we tested whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 39 publications
2
75
0
2
Order By: Relevance
“…This constitutes a significant metabolic stress, and it has been suggested that hibernators either constitutively express higher levels of antioxidant enzymes than non-hibernating species or that hibernators upregulate antioxidant enzymes to protect against oxidative damage. Indeed, hibernators have been reported to avoid oxidative stress associated with arousal (Ma et al 2005) and, similar to dwarf mice, show evidence of cellular stress resistance (Lindell et al 2005;Kurtz et al 2006;Dave et al 2006). We previously showed that 13-lined ground squirrels do not upregulate intracellular antioxidant enzyme activities in brain, heart or liver tissue during hibernation (Page et al 2009a).…”
Section: Discussionmentioning
confidence: 92%
“…This constitutes a significant metabolic stress, and it has been suggested that hibernators either constitutively express higher levels of antioxidant enzymes than non-hibernating species or that hibernators upregulate antioxidant enzymes to protect against oxidative damage. Indeed, hibernators have been reported to avoid oxidative stress associated with arousal (Ma et al 2005) and, similar to dwarf mice, show evidence of cellular stress resistance (Lindell et al 2005;Kurtz et al 2006;Dave et al 2006). We previously showed that 13-lined ground squirrels do not upregulate intracellular antioxidant enzyme activities in brain, heart or liver tissue during hibernation (Page et al 2009a).…”
Section: Discussionmentioning
confidence: 92%
“…Euthermic AGS are able to tolerate global ischemia, induced via cardiac arrest, without loss of CA1 neurons (Dave et al, 2005). Additionally, organs from TLS, whether in the euthermic or torpid state, tolerate cold ischemia-reperfusion injury (Lindell et al, 2005). Furthermore, acute hippocampal slices from euthermic TLS tended to tolerate OGD better than slices from rat at 361C; however, this tendency was not statistically significant (Frerichs and Hallenbeck, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Recent, repeated bouts of torpor were not necessary for OGD tolerance in summer euthermic AGS, suggesting that low body temperatures experienced during torpor do not augment OGD tolerance through hypoxic preconditioning. In other tissues, a seasonal effect of resistance to ischemic damage has been shown where summer animals show increased vulnerability to insult (Kurtz et al, 2006;Lindell et al, 2005). Further analysis of AGS sampled earlier in the summer season will be necessary to determine if seasonal factors associated with preparation for hibernation promote tolerance to OGD.…”
Section: Discussionmentioning
confidence: 99%